In Silico Identification of Potential Clovibactin-like Antibiotics Binding to Unique Cell Wall Precursors in Diverse Gram-Positive Bacterial Strains - Sierra-Hernandez, Olimpo; Saurith-Coronell, Oscar; Rodríguez-Macías, Juan; Márquez, Edgar; Ramón Mora, José; Paz, José L.; Flores-Sumoza, Maryury; Mendoza-Mendoza, Adel; Flores-Morales, Virginia; Marrero Ponce, Yovani; Barigye, Stephen J.; Martínez Ríos, Félix Orlando (MDPI, 2025)
The rise in multidrug-resistant bacteria highlights the critical need for novel antibiotics. This study explores clovibactin-like compounds as potential therapeutic agents targeting lipid II, a crucial component in bacterial cell wall synthesis, using in silico techniques. A total of 2624 clovibactin analogs were sourced from the PubChem database and screened using ProTox 3.0 software based on their ADME-Tox properties, prioritizing candidates with favorable pharmacokinetic profiles and minimal toxicity. Molecular docking protocols were then employed to assess the binding interactions of the selected compounds with lipid II. Our analysis identified Compound 22 as a particularly promising candidate, exhibiting strong binding affinity, stable complex formation, and high selectivity for the target. Binding energy analysis, conducted via molecular dynamics simulations, revealed a highly negative value of −25.50 kcal/mol for Compound 22, surpassing that of clovibactin and underscoring its potential efficacy. In addition, Compound 22 was prioritized due to its exceptional binding affinity to lipid II and its favorable ADME-Tox properties, suggesting a lower likelihood of adverse effects. These characteristics position Compound 22 as a promising candidate for further pharmacological development. While our computational results are encouraging, experimental validation is essential to confirm the efficacy and safety of these compounds. This study not only advances our understanding of clovibactin analogs but also contributes to the ongoing efforts to combat antimicrobial resistance through innovative antibiotic development. ©The authors ©International Journal of Molecular Sciences ©MDPI.
Abstract -- Introduction -- Results and Discussion -- Materials and Methods -- Conclusions -- Author Contributions -- Funding -- Institutional Review Board Statement -- Informed Consent Statement -- Data Availability Statement -- Acknowledgments -- Conflicts of Interest -- References.
Keywords: Clovibactin analogs; In silico; Lipid II; Molecular dynamics; ADME-Tox; Cell wall synthesis; Solvation energy; Ligand-receptor interactions; Binding affinity properties